Students’ Alternative Conceptions Concerning Threats and Vulnerability Due to Global Climate Change - Schuler, Stephan (Journal of Geography Education, 2009)
The investigation of students’ ideas and pre-instructional conceptions has become one of the most important fields of science education research. While some studies have investigated students’ mental models of the greenhouse effect already, only little is known about students’ ideas concerning the impacts of climate change and the vulnerability of people in different regions of the world. This study analysises students’ ideas about the vulnerability of people in Germany and Africa due to global climate change. The study is based on interviews with 25 students aged 18-19 from different schools in Germany. All in all the students in this study have basic conceptions about the different vulnerability of people in Germany and Africa, but there seems to be a tendency to emphasize natural hazards and natural conditions. There is a lack in the perception of socio-economic and political dimensions of vulnerability in terms of both sensitivity and adaptive capacity. For instructional settings it is important to take students ideas as a starting point and resource for further learning and to help students recognizing the structure and limits oft their own alternative conceptions.